The handbook of translation and cognition - John W. Schwieter; Aline Ferreira (Hoboken, New Jersey : Wiley Blackwell, 2020)
The Handbook of Translation and Cognition is a pioneering, state-of-the-art investigation of cognitive approaches to translation and interpreting studies (TIS)
Keywords: Electronic books